2021
DOI: 10.1371/journal.pone.0259336
|View full text |Cite
|
Sign up to set email alerts
|

The habitat-modifying red alga Ramicrusta on Pacific reefs: A new generic record for the Tropical Northwestern Pacific and the description of four new species from Guam

Abstract: The genus Ramicrusta (order Peyssonneliales) is a new record for Micronesia, with range expansions of Ramicrusta fujiiana and R. lateralis to Guam. In addition, four species (Ramicrusta adjoulanensis, R. asanitensis, R. labtasiensis, and R. taogamensis) are newly described from Guam using molecular and anatomical characters. Ramicrusta lateralis specimens from Guam share most anatomical features with the holotype description from Vanuatu, but the plants from Guam are more tightly adherent, rigid, and robust th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…The mitochondrial cytochrome c oxidase subunit I, COI-5P (roughly 664 bp), is a barcode marker that is regularly used for DNA barcoding of red algae [55] and was used for both the Corallinales and Peyssonneliales. The primer combination used to amplify COI-5P was TS_COI_F01_10 (5'-TCGARTCYCGTCTCTCTCG-3') [56] and the reverse primer, GWSRx [57]. Protocols for COI-5P amplification follow Mills & Schils [56].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrial cytochrome c oxidase subunit I, COI-5P (roughly 664 bp), is a barcode marker that is regularly used for DNA barcoding of red algae [55] and was used for both the Corallinales and Peyssonneliales. The primer combination used to amplify COI-5P was TS_COI_F01_10 (5'-TCGARTCYCGTCTCTCTCG-3') [56] and the reverse primer, GWSRx [57]. Protocols for COI-5P amplification follow Mills & Schils [56].…”
Section: Plos Onementioning
confidence: 99%
“…The primer combination used to amplify COI-5P was TS_COI_F01_10 (5'-TCGARTCYCGTCTCTCTCG-3') [56] and the reverse primer, GWSRx [57]. Protocols for COI-5P amplification follow Mills & Schils [56].…”
Section: Plos Onementioning
confidence: 99%
“…Of the 154 species found in this study, only ten of them matched (≥ 98% COI-5P similarity) sequences of described species, four of those were only described from Guam last year (Mills and Schils, 2021), suggesting that many of these CCRA species are possibly new to science. These findings are also consistent with recent studies that revealed extensive degrees of endemism and cryptic diversity within Guam's seaweed flora (Verbruggen and Schils, 2012;Gabriel et al, 2017;Leliaert et al, 2018;Gabriel et al, 2019;Mills and Schils, 2021;Vieira et al, 2022).…”
Section: Discussionmentioning
confidence: 76%
“…Of the 154 species found in this study, only ten of them matched (≥ 98% COI-5P similarity) sequences of described species, four of those were only described from Guam last year (Mills and Schils, 2021), suggesting that many of these CCRA species are possibly new to science. These findings are also consistent with recent studies that revealed extensive degrees of endemism and cryptic diversity within Guam's seaweed flora (Verbruggen and Schils, 2012;Gabriel et al, 2017;Leliaert et al, 2018;Gabriel et al, 2019;Mills and Schils, 2021;Vieira et al, 2022). Additionally, the CCRA diversity reported herein is greater than those of much larger coastal and oceanic ecosystems, including those documented in recent studies in New Zealand and Brazil (Twist et al, 2019;Sissini et al, 2021), in other barcoding blitzes in Hawaii, Taiwan, Tunisia, and…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation